Time Course of Changes in Sorafenib-Treated Hepatocellular Carcinoma (HCC) Cells Suggests Involvement of Phospho-Regulated Signaling in Ferroptosis Induction - Werth, Emily G. (Proteomics, 2020)
Ferroptosis is a form of regulated, non-apoptotic cell death characterized by excessive lipid peroxidation that can be triggered by inhibition of the cystine-glutamate antiporter, system X(c)(−). Sorafenib, an FDA-approved multi-kinase inhibitor drug that is used for treatment of hepatocellular carcinoma (HCC), has been shown to induce ferroptosis. Protein phosphorylation changes upon sorafenib treatment have been previously reported in patient studies and in cell culture. However, early phosphorylation changes during induction of ferroptosis are not reported. This work highlights these changes through a time course from 7 to 60 min of sorafenib treatment in human (SKHep1) HCC cells. A total of 6,170 unique phosphosites from 2,381 phosphoproteins were quantified, and phosphorylation changes occurred after as little as 30 minutes of sorafenib treatment. By 60 minutes, notable changes included phosphosites significantly changing on p53 (P04637), CAD protein (P27708), and proteins important for iron homeostasis, such as FTH1 (P02794), HMOX1 (P09601), and PCBP1 (Q15365). Additional sites on proteins in key regulatory pathways were identified, including sites in ferroptosis-related proteins, indicating the likely involvement of phospho-regulated signaling during ferroptosis induction.